22‐kyr‐Long Record of Surface Faulting Along the Source of the 30 October 2016 Earthquake (Central Apennines, Italy), From Integrated Paleoseismic Data Sets. Issue 8 (30th August 2019) - Cinti, F. R.; De Martini, P. M.; Pantosti, D.; Baize, S.; Smedile, A.; Villani, F.; Civico, R.; Pucci, S.; Lombardi, A. M.; Sapia, V.; Pizzimenti, L.; Caciagli, M.; et al.
Abstract: We integrate paleoseismic data sets along the Mt. Vettore‐Mt. Bove normal fault system rupturing at the surface in the 30 October 2016 Norcia earthquake. Through the analysis of new trenches from this work and a review of the preexisting data, we correlate events among trench sites along antithetic and synthetic fault splays. We recognize seven M 6.5, 2016 Norcia‐type (or larger) surface‐faulting events in the last 22 kyr, including 2016. Before 2016, one event occurred in the past two millennia (260–575 CE) and possibly corresponds to the event damaging Rome in 443 or 484/508 CE. Three previous events occurred between 10590 and 415 BCE, whereas the two oldest ones date between 19820 and 16540 BCE. The average recurrence time is 3, 360–3, 640 years for the last 22 kyr and 1, 220–1, 970 years for the last 4 kyr. We infer a minimum dip‐slip rate of 0.26–0.38 mm/year on the master fault in the central portion of the Mt. Vettore–Mt. Bove normal fault system and a dip‐slip rate of at least 0.10 mm/year on the southernmost portion. We infer a Middle–Late Pleistocene inception of the long‐term scarp of the investigated splays. The along‐strike variation of slip rates well reproduces the trend of the 2016 surface slip; thus, the time window exposed in the trenches is representative for the present fault activity. Based on trenching data, different earthquake rupture scenarios should be also considered for local hazard assessment. Key Points: We integrate paleoseismic datasets along the Mt. Vettore‐Mt. Bove normal fault system rupturing on 30 October 2016, M6.5, Norcia Earthquake Seven surface faulting events ruptured the Mt. Vettore-Mt. Bove fault systemin the past 22 kyr Paleoseismologic slip rates, recurrence intervals, and rupture scenarios contribute to the understanding of seismogenic processes in central pennines